The Influence of China in Central Asia : Examining Geostrategic orientations - Pazylova, Aktuigun; Garlick, Jeremy; Shakhanova, Gaziza; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
Central Asia plays an important role in China’s “New Great Game”. China’s focus on the region dictated by challenges of the modern world such as security threats, shortage of natural resources, and intensification of the international community regarding Human Rights protection. Central Asia as an unstable region is not in a position for equal partnership with China. The Xinjiang issue of China is the main deterrent of improved cooperation between China and Central Asia. This provides grounds for China to increase its geostrategic influence in the region via economic expansion. By employing mainly the theories of geopolitics, this thesis aims to illustrate how possibly China’s geostrategy affects political and socio-economic situations in the Central Asian states. With discourse analysis focused on explaining the Chinese perception of itself and the world, its intention and goal, I argue that China’s influence in Central Asia could result in unfavorable scenario for both.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses